A robust thermoelectric module based on MgAgSb/Mg3(Sb, Bi)2 with a conversion efficiency of 8.5% and a maximum cooling of 72 K. Issue 6 (16th May 2022) - Ying, Pingjun; Wilkens, Lennart; Reith, Heiko; Rodriguez, Nicolas Perez; Hong, Xiaochen; Lu, Qiongqiong; Hess, Christian; Nielsch, Kornelius; He, Ran
Abstract : Demonstration of a robust, tellurium-free thermoelectric module for near-room-temperature applications with a high conversion efficiency of 8.5% and a maximum cooling of 72 K. Abstract : The applications of thermoelectric (TE) technology around room temperature are monopolized by bismuth telluride (Bi2 Te3 ). However, due to the toxicity and scarcity of tellurium (Te), it is vital to develop a next-generation technology to mitigate the potential bottleneck in raw material supply for a sustainable future. Hereby, we develop a Te-free n-type compound Mg3 Sb0.6 Bi1.4 for near-room-temperature applications. A higher sintering temperature of up to 1073 K is found to be beneficial for reducing the electrical resistivity, but only if Mg is heavily overcompensated in the initial stoichiometry. The optimizations of processing and doping yield a high average zT of 1.1 in between 300 K and 573 K. Together with the p-type MgAgSb, we demonstrate module-level conversion efficiencies of 3% and 8.5% under temperature differences of 75 K and 260 K, respectively, and concomitantly a maximum cooling of 72 K when the module is used as a cooler. Besides, the module displays exceptional thermal robustness with a < 10% loss of the output power after thermal cycling for ∼32 000 times between 323 K and 500 K. These proof-of-principle demonstrations will pave the way for robust, high-performance, and sustainable solid-state power generation and cooling to substitute highly scarce and toxic Bi2 Te3 .